Maintainer/restorer identification for different CMS lines in sunflower (Helianthus annuus L.): MAINTAINER/RESTORER IDENTIFICATION IN SUNFLOWER - H P MEENA; M SUJATHA (Journal of Oilseeds Research, 2013)
Thirty one uniform and stable germplasm accessions of economic importance of sunflower were crossed with five cytoplasmic male sterile lines viz., CMS-234A, CMS-17A, CMS-338A, CMS-851A and ARM-243A in a Line x Tester fashion to study their maintainer or restorer reaction during kharif-2012 in a Randomized Block Design in two replications. The accessions TSG-22, TSG-24, ID-7, SCG-37, RHA-464 and ID-25 acted asrestorersfor allfive CMS lines. It was found that ID-33 of the restorer for ARM-243A was maintainer for other CMS lines. The use of stable germplasm with restorer behaviour in heterosis breeding programmes and those with maintainer behaviour in the development of new CMS lines through conversion has been suggested. The identification of new restorers to the good combiner CMS sources assembled should receive priority for hybrid synthesis.